Myostatin: Functional Divergence, Evolutionary Insights, and Therapeutic Potential: Myostatin: Functional Divergence, Evolutionary Insights, and Therapeutic Potential - Farhab, Muhammad (International Journal of Arts, Sciences and Education, 2025)
The transforming growth factor β (TGFβ) family members, growth differentiation factor 11 (GDF11) and myostatin (MSTN), share 89% sequence identity in their mature forms but exhibit distinct biological functions. While MSTN is a well-established negative regulator of skeletal muscle growth, the role of GDF11—particularly in postnatal development—remains controversial. This controversy stems in part from the perinatal lethality of Gdf11-null mice, which has led to reliance on recombinant proteins that may not fully replicate endogenous GDF11 activity. In contrast, genetic studies using knockout or conditional knockout models consistently suggest that GDF11 and MSTN play opposing roles in tissue development and homeostasis. This review explores the evolutionary divergence of GDF11 and MSTN, highlighting their distinct expression patterns and functions across species. We discuss their proteolytic processing, signaling mechanisms, and physiological roles in development, adulthood, and aging. Additionally, we evaluate the therapeutic potential of recombinant GDF11 and the implications of MSTN inhibition. Notably, while the mature domains of GDF11 and MSTN are highly conserved, their prodomains exhibit significant divergence, suggesting unique regulatory mechanisms for GDF11. This comprehensive analysis aims to clarify the functional distinctions between GDF11 and MSTN and their relevance in health and disease.